(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Multi location field trials were conducted during the 2019/2020 dry season at Teaching and Research Farm of Federal University Dutsin-Ma (Badole) 11058`N, 80 26`E and 475m above sea level and Kugado Fadama site (110 33 N, 80 23 E and 481m above Sea level). Treatments consisted of three varieties of groundnut (SAMNUT 24, SAMNUT 25 and SAMNUT 26), 3 intra-row spacing (15, 20 and 25cm), and three irrigation intervals (3, 6 and 9days) replicated three times. The treatments were factorized and laid out in a randomized complete block design (RCBD). Results from the study revealed that groundnut variety had significant (P≤0.05) effect on the performance of groundnut at the two locations. SAMNUT 24 significantly (P≤0.05) outperformed SAMNUT 26 and 25 respectively in terms of stand establishment count, plant height, canopy spread, pod number per plant, pod weight per plant, and haulms weight per plant at the two locations. Intra-row spacing of 15cm significantly (P≤0.05) outperformed 20 and 25cm respectively however, 6days irrigation interval on growth and 3days irrigation interval on yield parameters recorded a significant (P≤0.05) effect at Badole while at Kugado 6days for growth and 9days irrigation interval for yield parameters was significant. The study revealed that SAMNUT 24, intra-row spacing of 15cm, 6days irrigation interval on growth and 3 days on yield parameters at Badole and Kugado SAMNUT 24, intra-row spacing of 15cm, 6days irrigation interval on growth and 9days irrigation interval on yield component proved to be most effective